ANALYSIS OF PROSPECTS OF CORN GROWING IN UKRAINE - Бахмат, М. І.; Кирилюк, Р. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The aim of this paper is to analyze the main issues of modern development and the prospects for the maize culture in Ukraine; search for possible ways to improve new methods and technologies to improve the dissemination of maize culture in Ukraine. Consider the demand of recent years in Ukraine on simple hybrids of corn. Analyzes the practical training which indicates that simple hybrids are characterized by high yield, adaptability, resistance to disease, the choice of the main Morfobiologic High quality and performance. The analysis of the competitive ability of maize culture and its growing potential prospects in Ukraine;was analyzed examples and ways of promoting future development technology of growing corn; Advantages over other cultures of corn crops; were set out the basic terms multifaceted, diverse perspectives of spreading the culture of maize in Ukraine; was given the need for new conditions, strategy development and improvement through study and justification of new technologies cultivation of maize.was Analyzed the maize market culture influenced by various factors. Introduction of the achievements of modern genetics and azonal technological developments are the main levers of struggle against water and temperature stress of maize. Their creative combination will help stabilize grain production and substantially reduce dependence on weather conditions.